Using the given equation y-3 = 3/4(x+2)
Give Y a value and then solve for x:
If y = 0 the equation is now:
0 -3 = 3/4(x+2)
Solve for x:
-3 = 3/4x + 1.5
-4.5 = 3/4x
x = -4.5 / 3/4
x = -6
So the first point would be (-6,0)
Now make x 0 and solve for y:
y -3 = 3/4(0+2)
y-3 = 0 + 1.5
y = 4.5
So the 2nd point would be (0,4.5)
You are close, but the dot you have on y=4, needs to be moved up to 4.5.
Answer:
Correct integral, third graph
Step-by-step explanation:
Assuming that your answer was 'tan³(θ)/3 + C,' you have the right integral. We would have to solve for the integral using u-substitution. Let's start.
Given : ∫ tan²(θ)sec²(θ)dθ
Applying u-substitution : u = tan(θ),
=> ∫ u²du
Apply the power rule ' ∫ xᵃdx = x^(a+1)/a+1 ' : u^(2+1)/ 2+1
Substitute back u = tan(θ) : tan^2+1(θ)/2+1
Simplify : 1/3tan³(θ)
Hence the integral ' ∫ tan²(θ)sec²(θ)dθ ' = ' 1/3tan³(θ). ' Your solution was rewritten in a different format, but it was the same answer. Now let's move on to the graphing portion. The attachment represents F(θ). f(θ) is an upward facing parabola, so your graph will be the third one.
Answer:
1. d 2. d 3. a
Step-by-step explanation:
1. factor
((w-4)(w-6))/((w-5)(w-6))+8/(w-5)
solve
(w-4)/(w-5)+8/(w-5)
(w+4)/(w-5), so d
2.factor
((b+2)(b-4))((b+2)(b-1))-6/(b-1)
solve
(b-4)/(b-1)-6(b-1)
(b-10)/(b-1), so d
3. (2/5t-3/3t)/(1/2t+1/2t)
(2/5t-1/t)/(2/2t)
(2/5t-1/t)/(1/t)
t(2/5t-1/t)
2/5-1=-3/5, so a
Answer:
i think its option ccc ydi aeg
because angle y is congruent to angle a
angle i is congruent to angle d
The sequence is incrementing by
![{2}^{n}](https://tex.z-dn.net/?f=%20%7B2%7D%5E%7Bn%7D)
Therefore, the sixth number is
![{2}^{6}](https://tex.z-dn.net/?f=%20%7B2%7D%5E%7B6%7D%20)
Which is 64.